Knowledge and Practice of Documentation in Labour among Healthcare Professionals in a Tertiary Healthcare Facility, South- South, Nigeria - Frank, Maureen Dike; Akpan-Idiok, Paulina Ackley; Chinenye, Chukwu (Disease and Health: Research Developments Vol. 4, 2025)
Background: Documentation is a fundamental and vital communication tool among healthcare professionals. It is an essential part of nurse/ midwife that has clinical and legal implications for the client nurse/ midwife as well as the health care institution. This study assessed determinants of documentation in labour among healthcare professionals in a tertiary healthcare facility in South-South, Nigeria. Methods: This is a descriptive cross-sectional study with a sample size of 102 purposively selected healthcare professionals (nurses/midwives). The instrument for data collection was self-structured questionnaire. Data collected were analysed using statistical package for social sciences (SPSS) version 23 and presented in simple percentage and frequency table. Results: The findings of the study showed that nurses had good knowledge of documentation in labour. Determinant factors influencing documentation includes; time, their poor attitude towards documentation (terming documentation to be unnecessary), and few number of midwives working in a shift. Conclusions: Findings concluded that respondents have good knowledge of documentation, however this has not translated into practice. Also, there are factors that influence this practice among the respondents. Recommendations: It was recommended that training and workshops on the importance of documentation should be organized regularly to create more awareness on documentation; to encourage and promote its practice; identify factors hindering its use as well as provide strategies for overcoming these factors. Also, more staff should be assigned to clients and the shift adjusted to shorter hours to prevent fatigue and tediousness.